DISTAL REVASCULARIZATION AND INTERVAL LIGATION PROCEDURE FOR THE TREATMENT OF DIALYSIS ACCESS INDUCED STEAL SYNDROME - Usman, Rashid; Jamil, Muhammad; Khan, Aleena Ahmed; Talat, Afnan (Journal of Ayub Medical College Abbottabad, 2020)
Background: We aim to share our experience of the efficacy of Distal Revascularization and Interval Ligation (DRIL) in alleviating ischemic symptoms of dialysis access induced steal syndrome (DAISS) while preserving the original access. Methods: In this multicentre study, all consecutive patients with DAISS undergoing DRIL over a period of 3 years were included. Results: A total of 25 DRILs were included. Mean age was 37.8±SD 7.8 years and 52% (n=13) were females. Out of 25 patients; 88% (n=22) had more than one of the following ischemic symptoms: coolness (96%), pain (88%), paresthesia (80%), and discoloration (44%). Significant improvement following DRIL was noted in paraesthesia (86%, p-value 0.00), pain (85%, P value 0.00), coolness (83%, p-value 0.00). There was significant improvement in distal blood flow following DRIL, reflected by increase in the Aggregate Peak Systolic Velocities (PSV) in forearm vessels (PSV aggregate pre-op 39cm/s: PSV aggregate post-op 58 cm/s; p-value 0.01). The cumulative patency of DRIL graft was 96% at 3 months, 84% at 6 months and 76% at 1 year. Conclusion: Distal Revascularization and Interval Ligation significantly improves circulation to the distal limb and reduce ischemic symptoms thus making it a procedure of choice for treatment of DAISS. Keywords: Hand ischemia; Arterio-venous fistula; DRIL; Steal syndrome; Dialysis access